Swedish student teachers’ perceptions of consequences of the teacher shortage for their future profession - Ulla Damber; Lena Boström (Social Sciences and Humanities Open)
The current teacher shortage is a global phenomenon, and it has spurred research from various perspectives. However, there is limited research on student teachers' perceptions, in particular in the Nordic countries. This study, therefore, is based on 75 student teachers' perceptions of the teacher shortage and its consequences for their future profession, their students, and society at large. Empirical data was analysed with reflexive thematic analysis and following Bronfenbrenner's ecological systems theory. The answers show great concern from all three perspectives. The conclusions are that the teacher shortage must be understood and addressed on a broad front that includes student teachers.